TASHWIR IN THE CONTEXT OF HADITH AND ITS RELEVANCE TO THE PRESENT - Isman, Ainul Fatha; Firdaus, Firdaus; Nufus, Ilma Silmi; Chuzaemah, Siti (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2024)
The opinions of the scholars regarding the understanding of hadiths regarding tashwir are very diverse. Meanwhile, the tashwir concept is currently being widely implemented in people’s lives. Therefore, a more in-depth study is needed to understand these tashwir hadiths. The purpose of this study is to describe the tashwir hadith and analyze the hadith with its relevance to the present context. This research method uses a qualitative descriptive study approach based on primary and secondary sources. The research results show that tashawwur activities in several hadiths are not permitted. However, the main reason for this prohibition is that it is vulnerable to polytheism, whether in the form of worshiping idols or competing with Allah as the creator. If studied in the current context, the prohibition of tashwir is inappropriate because it has a different purpose when narrated. Tashawwur in the modern er, needs to refer to the benefit dimension as a basis for consideration in current implementation. Currently, tashwir functions as art, decoration, a medium for preaching, and even a place for some people to work to fulfill their needs. Therefore, rejecting tashwir in Islam depends on its function and purpose. The implications of this research are expected to provide a new paradigm regarding the practice of tashawwur in today’s modern life, which is very diverse and has differences from the past.[Pendapat para ulama terhadap pemahaman hadis-hadis tentang tashwir sangat beragam. Sedangkan konsep tashwir pada masa kini sedang marak diimplementasikan dalam kehidupan masyarakat. Oleh karena itu diperlukan telaah yang lebih mendalam untuk memahami hadis-hadis tashwir tersebut. Tujuan penelitian ini menguraikan hadis-hadis tashwir dan menganalisis hadis tersebut dengan relevansinya pada konteks masa kini. Metode penelitian ini menggunakan deskriptif kualitatif dengan pendekatan studi literatur berdasarkan sumber primer dan sekunder. Hasil penelitian menunjukkan bahwa kegiatan tashawwur dalam beberapa hadis tidak diperbolehkan. Namun, larangan tersebut memiliki alasan utama yaitu rentan terhadap kemusyrikan, baik berupa menyembah berhala atau menandingi Allah sebagai pencipta. Jika dikaji dalam konteks saat ini maka pelarangan tashwir ini kurang tepat karena memiliki tujuan yang berbeda pada saat diriwayatkannya. Tashawwur di era modern perlu merujuk pada dimensi kemaslahatan sebagai dasar pertimbangan dalam implementasi masa kini. Saat ini tashwir berfungsi sebagai seni, hiasan, media dakwah, bahkan sebagai wadah pekerjaan sebagian orang untuk memenuhi kebutuhannya. Oleh karena itu, untuk menolak tashwir dalam Islam tergantung pada fungsi dan tujuannya. Implikasi penelitian ini diharapkan mampu memberikan paradigma baru tentang praktik tashawwur pada kehidupan modern saat ini yang sangat beragam dan memiliki perbedaan di masa lampau.]